Characteristics of an `effective` tackle outcome in Six Nations rugby - van Rooyen, M.; Yasin, N.; Viljoen, W. (European Journal of Sport Science, 2014)
Rugby is a full contact sport that frequently comprises of tackle situations between two or more players. At present there is no research available that has quantified the defining elements that lead to `effective` tackle outcomes in matches or whether they factor in the success or failure of teams. The purpose of this study was to understand the actions of the tackler during contact with the ball-carrier and relate them to the `effectiveness` of the tackle outcome, during rugby match play. Matches (n=15) from the 2007 Six Nations Tournament were analysed. `Effective` tackling was assessed with regards to the territorial change of the ball-carrier from the point of contact with the tackler to completion of the tackle, and characterised in terms of the tackler's body position, the angle at which the tackler approached the tackle and the outcome. The `less effective` tackle is 34% more prevalent (P<0.001) than the `effective` tackle during match play. Winning teams were involved in fewer tackle situations and made 3% more `effective` tackles and 4% fewer `less effective` tackles than losing teams. `Effective` tackle outcomes were found to have a greater percentage of the player's torso leaning forward and oblique angle approaches to the ball-carrier. The difference in the frequency of upright and back foot characteristics differentiated winning from losing teams. This was the first study to describe the characteristics of an `effective` tackle outcome and serves as a basis from which further research can be done on the tackle situation.